PENGARUH METODE DEBAT TERHADAP KETERAMPILAN BERTANYA DALAM PEMBELAJARAN IPS - Ded Nurhumaedah, - (2018)
Keterampilanbertanyasangatpentingdikembangkanpadapesertadidiktingkat SMP.Karenapadaabad 21 tantangangenerasimudabukanhanyauntukmenciptakansesuatutanpamemikirkandampaknegatifnya, tetapitantangansesungguhnyaadalahmenyeimbangkandanmenjagakelestariankehidupanmanusiadibumidariberbagaipersoalan yang ada.Denganberusahamengembangkanketerampilanbertanyapesertadidik, yang bertujuanmeningkatkankemampuanberfikirkritis, agar pesertadidikmulaidapatmemahamidanmemecahkanpermasalahan-permasalahandalamkehidupansosialdisekitarnya.AlasanpenelitianmenerapkanmetodedebatpadapesertadidikkelasVIII 3 adalah, agar dapatmengembangkanketerampilanbertanyapesertadidik yang rendah,sertamengarahkanketidakkondusifanpembelajarankarenapesertadidik yang ramaipadasaatpembelajaranmenggunakanmetodekonvensional. MelaluiPenerapanmetodedebataktifdalampembelajaran IPS, dapatmerangsangpesertadidikmenjadilebihagresifuntukmengemukakanpendapatdantidakmerasamalu.Metodepenelitian yang digunakanadalah quasi eksperimendenganmembandingkanmetodepembelajaran yang berbedayaitumetodedebatdanmetodetanyajawab. Hasilpenelitianiniberdasarkanpengambilan data melaluikuesionersebelumdansesudahditerapkanperlakuan.Melalui data yang diperolehpadasaatpenelitian, penerapanmetodedebatdalampembelajaran IPS dapatmeningkatkanketerampilanbertanyapesertadidiksebesar 5.02%, dari 22.94% menjadi 27.96%. Sedangkan di kelas yang menerapkanmetodebertanyakenaikannyahanyasebesar1.48% dari 23.56% menjadi 25.53%.datatersebutmenunjukanbahwaterdapatpeningkatan yang signifikandalamketerampilanbertanyapesertadidik yang telahditerapkanmetodedebatdibandingkanmetodetanyajawab, karenadalamujihipotesismenghasilkannilai sig (2-tiled) 0.002 < 0.05. ;---Very important questioning skills are developed in junior high school students. Because in the 21st century the challenges of the young generation are not only to create something without thinking about its negative effects, but the real challenge is to balance and preserve the sustainability of human life on earth from the various problems that exist. By trying to develop students' asking skills, which aims to improve the ability to think critically, so that students begin to understand and solve problems in the social life around them. The reason for applying the debate method to students in class VIII 3 is to develop students' low-asking skills, and to direct unfavorable learning because students are busy when learning using conventional methods. Through the application of active debate methods in social studies learning, can stimulate students to be more aggressive to express opinions and not feel ashamed. The research method used was quasi-experimental by comparing different learning methods, namely the debate method and the question and answer method. The results of this study are based on data collection through questionnaires before and after treatment is applied. Through the data obtained at the time of the study, the application of the debate method in social studies learning can improve the students' questioning skills by 5.02%, from 22.94% to 27.96%. Whereas in the class that applies the method, the increase is only 1.48% from 23.56% to 25.53%. The data shows that there is a significant increase in the questioning skills of students who have applied the debate method compared to the question and answer method, because in hypothesis testing produces sig (2-tiled) value 0.002 <0.05.